Engineering dextran-based scaffolds for drug delivery and tissue repair. (November 2012) - Sun, Guoming; Mao, Jeremy J
Owing to its chemically reactive hydroxyl groups, dextran can be modified with different functional groups to form spherical, tubular and 3D network structures. The development of novel functional scaffolds for efficient controlled release and tissue regeneration has been a major research interest, and offers promising therapeutics for many diseases. Dextran-based scaffolds are naturally biodegradable and can serve as bioactive carriers for many protein biomolecules. The reconstruction of the in vitro microenvironment with proper signaling cues for large-scale tissue regenerative scaffolds has yet to be fully developed, and remains a significant challenge in regenerative medicine. This paper will describe recent advances in dextran-based polymers and scaffolds for controlled release and tissue engineering. Special attention is given to the development of dextran-based hydrogels that are precisely manipulated with desired structural properties and encapsulated with defined angiogenic growth factors for therapeutic neovascularization, as well as their potential for wound repair.